Preparation and Characterization of Lanthanide (III) Chloride Complexes with 5-Methylbenzotriazole (MBTAZ) - Prafull Sharma; Anjali Soni (International Journal of Research in Chemistry and Environment (IJRCE), 2020)
A new series of complexes of lanthanide (III) complexes with 5-Methylbenzotriazole (MBTAZ) have been prepared in non-aqueous media and characterized by various physico-chemical studies, viz-elemental analysis, molecular weight, electrolyte conductance and I.R. Spectra etc. . The primary purpose of the paper is synthesizing new complexes of lanthanides (Ln= La, Nd, Tb, Dy or Ho) chlorides, with 5- aminothiazole ligand. Studying their properties by various physicochemical techniques. Attempting to understand their bonding and structural characteristics A comprehensive study on their synthasis, physico-chemical properties and structural characteristics is, therefore, worth investing. Coordination chemistry of aromatic amines is of particular interest because of the variation in stoichiometry in which these ligands may be bound to a metal ion. Thus in present investigation new complexes with aromatic amines such as 2-aminothiazole has been synthesized.